PENERAPAN PENGGUNAAN PEMBAYARAN DIGITAL QRIS PADA UMKM - Anjas Juliansyah Siregar; Azhela Dwi Aryani; Dian Aulya Utami; Nurbaiti Nurbaiti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The implementation of QRIS (Quick Response Code Indonesia Standard) is a digital solution that supports the growth of UMKM in Indonesia. The research method was carried out using a descriptive qualitative approach. Research data comes from search results from various trusted sources, including official websites, theses and national scientific journals that are relevant to the research topic. QRIS makes it easy for UMKM to conduct non-cash transactions, addressing customer convenience and security. This study is to analyze the benefits and impacts of QRIS on UMKM turnover and operations. The results of the discussion also show that QRIS is able to increase operational efficiency through an easy-to-use online payment system that records transactions automatically, which helps UMKM in financial management. In addition, QRIS also increases security by reducing the risk of losing cash and using counterfeit money. However, there are obstacles in implementing QRIS, such as admin fees and the duration of disbursement of funds which are considered burdensome for UMKM.